Spaces of (self)care: domesticity in the face of residential vulnerability - Emma Peltier (GéoProximitéS)
This article explores the relationship between care and domestic space, based on the situation of residential vulnerability experienced by women situated at the intersection of gender and anti-Roma racism. Using concepts forged by feminist philosophers, this text sets out three micro-geographical scales of care in domestic space: furnishing, dressing and hospitality. This focus enables to understand domestic space not only as a vector of patriarchal domination but also as a lever of individual and collective agency.